La prise de position éditoriale - Gilles Gauthier (Communication)
This article is concerned with editorial argumentation.  The object, with the help of operational definitions of argument and opinion, is to measure the role of argumentation in the positions taken in editorials by the Québécois press.  A procedure of identification of argument and opinion is then finely tuned and applied to an editorial corpus of Québécois dailies.  This analysis reveals significant regularities in the papers studied in spite of important differences between editorialists.